Zmĕny klinických a epidemiologických charakteristik invazivního meningokokového onemocnĕní v západních Cechách v souvislosti s výskytem invazivního klonu Neisseria meningitidis - Struncová, V; Pazdiora, P; Valchová, M; Sedlácek, D; Fránová, D; Bárta, R; Musílek, M; Krízová, P (Epidemiologie, mikrobiologie, imunologie, 1997)
The authors analyzed the incidence of meningococcal diseases in the West Bohemian region in 1982-1996. The draw attention to changes of clinical and epidemiological characteristics of the disease which appeared in 1994 in conjunction with a new invasive clonus of Neisseria meningitidis C:2a:P1.2, P1.5, ET-15/37. While in 1982-1993 invasive meningococcal diseases had in 75% the course of meningitis with a relatively low fatality (4%), during the subsequent period a marked change occurred. Since 1994 the disease took in the West Bohemian region in 58% the course of sepsis with a fatality of 16%. 25% cases of meningococcal meningitis were diagnosed combined sepsis and meningitis in 17%. The disease lost its seasonal character and the authors confirmed the highest incidence of the disease in the age group from 15-19 years and 0-4 years. Neisseria meningitidis group C was detected in 1994-1996 in 73% and the invasive clone C:2a:P1.2, P1.5, ET-15/37 in 62%.
Keywords: dospělí; Infant; dítě; předškolní dítě; Adult; Adolescent; meningokokové infekce; lidé; Meningococcal Infections; kojenec; Czech Republic; Neisseria meningitidis; Child, Preschool; Česká republika; lidé středního věku; Child; Middle Aged; mladiství; Humans